Correction: Visualising mouse neuroanatomy and function by metal distribution using laser ablation-inductively coupled plasma-mass spectrometry imaging. Issue 11 (10th September 2015) - Paul, Bence; Hare, Dominic J.; Bishop, David P.; Paton, Chad; Nguyen, Van Tran; Cole, Nerida; Niedzwiecki, Megan M.; Andreozzi, Erica; Vais, Angela; Billings, Jessica L.; Bray, Lisa; Bush, Ashley I.; et al.
Abstract : Correction for 'Visualising mouse neuroanatomy and function by metal distribution using laser ablation-inductively coupled plasma-mass spectrometry imaging' by Bence Paul et al., Chem. Sci., 2015, DOI: 10.1039/c5sc02231b.